Scared Straight? Threat and Assimilation of Refugees in Germany - Philipp Jaschke; Sulin Sardoschau; Marco Tabellini (Institute of Labor Economics (IZA), 2021)
This paper studies the effects of threat on convergence to local culture and on economic assimilation of refugees, exploiting plausibly exogenous variation in their allocation across German regions between 2013 and 2016. We combine novel survey data on cultural preferences and economic outcomes of refugees with corresponding information on locals, and construct a threat index that integrates contemporaneous and historical variables. On average, refugees assimilate both culturally and economically. However, while refugees assigned to more hostile regions converge to local culture more quickly, they do not exhibit faster economic assimilation. We provide evidence consistent with the hypothesis that refugees exert more assimilation effort in response to local threat, but fail to successfully integrate because of higher discrimination by locals in more hostile regions.
Keywords: F22; J15; Z10; 330; migration; refugees; culture; assimilation; identity